"Legal exposure" lifting the corporate veil in deciding matrimonial property - Abd Ghadas, Zuhairah Ariff; Ibrahim, Norliah (2010)
The doctrine of lifting of corporate veil is a legal principle applied by the court to set aside the separate legal entity of a company in order to discover the truth behind the veil of corporation. Despite its frequent use, the doctrine of lifting the corporate veil is only applied by the court under justified circumstances, for example when physical attributes of the company is required, in cases involving fraud or when the company is used as a sham, alter ego or agent of the owner/members for certain purposes